PENGEMBANGAN MEDIA FLIPBOOK BERBASIS REALISTIC MATHEMATICS EDUCATION PADA KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK - Karsim, Karsim; Ratnaningsih, Nani; Rahayu, Diar Veni (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2023)
Teacher’s lack of interactive learning media and abstract mathematics learning materials results in low mathematical communication skills as indicated by students' answers in solving math problems. Flipbook media is one of the interactive and interesting learning media in learning mathematics which accommodates the principles of the Realistic Mathematics Education (RME) approach. This study aims to determine the procedure for developing RME-based flipbook media and to determine students' mathematical communication skills after using the media developed on circle material. This type of research is R & D (Research & Development) research using the 4D development model (Define-Design-Develop-Disseminate). The subjects in this study were 3 mathematics teachers, 6 students taken from each class VIII outside class VIII-E, 2 material experts, 2 media experts and 32 students from class VIII-E SMPN 3 Banjar. Data collection techniques are observation, interviews, questionnaires and tests. The data analysis technique used is descriptive statistical analysis and qualitative data analysis. Based on the analysis of the results of the mathematical communication ability test, as many as 31.25% of students showed a level of mathematical communication ability in the